An Intercultural Approach to English Language Teaching - Corbett, John, 1959- (Bristol: Multilingual Matters, 2022)
"This is a thoroughly revised, updated and expanded edition of a practical introduction to intercultural education for teachers of English as a second language. This new edition addresses developments in the field since the publication of the 1st edition, including the impact of online resources for English language education"--
Linguistic and anthropological perspectives on culture -- From intercultural communication to literary, media and cultural studies -- Defining intercultural communicative competence -- Implementing an intercultural approach to ELT -- Culture and conversation -- Developing an ethnographic frame of mind -- Interviewing skills for the intercultural learner -- Virtual ethnographies : intercultural telecollaboration -- Developing visual literacy -- Using literary, media and cultural studies -- Assessing intercultural communicative competence -- Further prospects for intercultural language education.
Keywords: English language -- Study and teaching -- Foreign speakers; Intercultural communication; Multicultural education; Language and culture